Pengaruh Penerimaan Pajak Restoran Terhadap Pendapatsan Asli Daerah Kota Bekasi - Hartanti Hartanti; Annisa Puspa Nabilah (LPPM Universitas Bina Sarana Informatika, 2023)
Bekasi City is one of the metropolitan cities that is experiencing rapid development, especially in the industrial sector. This development has also encouraged the emergence of various new restaurants, which contribute to increasing the potential for restaurant tax revenue. Restaurant tax itself is a tax on services provided by restaurants and is an important component of Regional Original Income (PAD). This study aims to determine the effect of restaurant tax revenue on PAD in Bekasi City. The research was conducted at the Bekasi City Regional Revenue Agency, using secondary data obtained through observation, documentation, and literature studies that were systematically arranged according to the research objectives. The data analyzed included restaurant tax revenue and Bekasi City PAD during the period 2020–2023, with a total of 48 observation data. The research method used is a quantitative approach. The data analysis techniques used include correlation coefficient tests, determination coefficient tests, and simple linear regression, with the help of SPSS version 27 software. The results of the study indicate that there is a positive relationship between restaurant tax revenue and Bekasi City PAD with a correlation coefficient value of 0.388, or 38.8%. Meanwhile, the results of the determination test indicate that restaurant tax contributes 15.1% to PAD variability. The regression significance test produces a calculated t value of 2.855> t table 2.011, with a significance level of 0.006 < 0.05, which means that the effect is statistically significant. The regression equation obtained is Y = 127,596,950,108.561 + 3.039X.